Effect of Lentiviral Vector-Mediated CXCR4 Gene Overexpression on Mesenchymal Stem Cell Homing Capacity - Chen, Wei; Zhou, Dian; Li, Ya-Ru; Liu, Jun-Xiu; Wang, Xiang-Min; Zhu, Feng; Xu, Kai-Lin (Zhongguo shi yan xue ye xue za zhi, 2018)
To explore the effects of lentiviral-mediated CXC chemokine receptor-4（CXCR-4）gene over-expression on the homing capacity of mesenchymal stem cells（MSC）in vivo. The MSC overexpressing CXCR-4 were constructed by using the lentiviral vector-mediated mouse MSC overexpressing the CXCR-4 gene. The BALB/c mice were divided into 3 group: simple radiation group（TBI）in which mice exposed to total body irradiation, then were infused with normal saline; EGFP-MSC group in which mice were infused with MSC（5×10 ）transducted by EGFP via tail vein after TBI; and CXCR-4-MSC group in which mice were infused with MSC (5×10 ) simultaneously carraying EGFP and CXCR-4 gene via tail vein after TBI. The mice were sacrified at 24 hours after infusion, the frozen sections were prepared to detect the distribution of infused MSC. Furthermore, the numbers of MSC homing into spleen and bone marrow was detected by flow cytometry, and the level of stromal cell-derived factor-1(SDF-1) was detected by ELISA. The frozen section showed that the